2007
DOI: 10.4049/jimmunol.179.4.2261
|View full text |Cite
|
Sign up to set email alerts
|

Class IA Phosphoinositide 3-Kinase Modulates Basal Lymphocyte Motility in the Lymph Node

Abstract: Recruitment of PI3K to the cell membrane is an indispensable step in normal lymphocyte proliferation and activation. In this study we identify PI3K as an important signaling molecule for maintaining basal T and B lymphocyte motility and homing in the intact lymph node. Pharmacological inhibition of PI3K catalytic isoforms exerted broad effects on basal lymphocyte motility, including changes in homing kinetics, localization of B cells within the lymph node, and reduced cell velocities. Lymphocytes deficient in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 43 publications
3
39
0
Order By: Relevance
“…The discrepancy to other published reports 32,33 is unclear at the moment but could be the result of different transgenic models. Although PI3K␦ activity is required for full ERK phosphorylation downstream TCR signaling, 61,62 expression of inactive PI3K␦ did not reduce CCL21-mediated costimulation in the experimental model used here. PI3K activity thus appears dispensable for CCL21-mediated costimulation in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…The discrepancy to other published reports 32,33 is unclear at the moment but could be the result of different transgenic models. Although PI3K␦ activity is required for full ERK phosphorylation downstream TCR signaling, 61,62 expression of inactive PI3K␦ did not reduce CCL21-mediated costimulation in the experimental model used here. PI3K activity thus appears dispensable for CCL21-mediated costimulation in vitro.…”
Section: Discussionmentioning
confidence: 60%
“…In lymph node slices imaged by epifluorescence microscopy, pretreatment with wortmannin had no effect on T cell motility (57). In contrast, recent work from our group, in collaboration with David Fruman (70), showed that wortmannin treatment resulted in a significant decrease in T and B cell motility in lymph node explants ( Table 2). Although class IA and IB catalytic subunits (p110δ and p110γ, respectively) had previously been shown to be involved in lymphocyte chemotaxis and homing (71,72), and p110γ is indispensable for neutrophil chemotaxis (73-75), p110γ deletion had only a minor effect on T cell motility and did not alter velocity or B cell motility (76).…”
Section: Than In T Cells (66)mentioning
confidence: 89%
“…This effect does not appear to be subset restricted, as both CD4 + and CD8 + memory T cells display similar requirements for p110δ activity to be recruited in an antigen-dependent manner. In this context, class I PI3K regulatory subunit p85 has been shown to contribute to spontaneous lymphocyte motility in the lymph node (18). As PI3Ks have been implicated in signaling pathways leading to integrin activation, it is possible that p85 activity may be required for efficient cell-cell interactions in the lymph nodes.…”
Section: Discussionmentioning
confidence: 99%